2014
DOI: 10.1590/1413-78522014220200798
|View full text |Cite
|
Sign up to set email alerts
|

A manual method to obtain platelet rich plasma

Abstract: OBJECTIVE: This study is to report a manual method to obtain platelet rich plasma (PRP). METHODS: For this study 61 ml of peripheral blood was obtained and submitted to centrifugation at 541g for 5 min. The centrifugation separates the blood into three components: red blood cells, buffy coat and platelet rich plasma. Blood and platelet rich plasma samples were sent to the Hospital's Laboratory and platelets and leukocytes were measured. RESULTS: A sample of 637 blood donors was evaluated. The platelet yield ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The gel is injected to the desirable site. It should be noted that there is a difference in platelet quantity: platelet and WBC count is higher in younger people and higher in females compared to males [15,21,22]. [16,23].…”
Section: The Techniquementioning
confidence: 99%
“…The gel is injected to the desirable site. It should be noted that there is a difference in platelet quantity: platelet and WBC count is higher in younger people and higher in females compared to males [15,21,22]. [16,23].…”
Section: The Techniquementioning
confidence: 99%
“…Another study proved that centrifugation of 541 g for 61 mL of whole blood at 5 minutes was optimal for obtaining high platelet in the sample. 14 In this study, we also included a single centrifugation technique that is commonly used. The platelet counts in PRP can affect and positively correlate with the concentration of growth factors and better clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…It could be argued that the age and gender have some effect on PRP. For instance, studying 637 people, Marques et al found that platelet count in women and young people were higher than in men and older people ( 29 ).…”
Section: Discussionmentioning
confidence: 99%